Effect of wire-EDM parameters on machining characteristics of titanium alloy (Ti6AI4V) using Taguchi method - Jaafar, Noor Azam (2013)
Wire electrical discharge machining (WEDM) is a modification of electro discharge machining (EDM) which has been widely used for a Jong time in producing mould, die and other machine parts of conductive materials. Capability of cutting variety of conductive materials with intricate shapes makes it important in the market. Now, WEDM is extensively used in the field of mould making, medical, aerospace, and automobile industries. But, selection of optimum machining parameter is challenging task in WEDM due to the presence of a large number of process variables and stochastic process mechanism. ln this study, WEDM of Titanium alloy (Ti6Al4V) is experimentally studied. The influence of pulse duration, pulse interval, servo voltage and ignition pulse current on material removal rate, surface roughness and kerf width is studied using Taguchi method. Analysis of varience method (ANOV A) will be used for recognizing the level of significance of WEDM cutting parameter for optimizing the above mentioned machining performance. Finally the Jesuits are particularly useful for machine manufacturers and researchers to determine the best combination of parameters which lead to optimize the machining performance .